2000
DOI: 10.4133/jeeg5.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Hydraulic Conductivity and Porosity of Soils from Spectral Electrical Response Measurements

Abstract: A procedure is developed to estimate the hydraulic conductivity and porosity of soils from the laboratory measurements of their frequency dependent electrical response (FDER) using inversion schemes and regression models. The FDER (resistivity and phase spectra) of a soil contains valuable information about its porosity, hydraulic conductivity, texture and fluid properties. In this study the FDER of the soil is modeled as a heterogeneous system using the multi-Cole-Cole model. The intrinsic parameters, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The Cole-Cole model (Cole and Cole, 1941) has been found to be very useful for interpreting spectral IP (SIP) data in terms of parameters, such as chargeability and time constant, which in turn have been used to estimate various subsurface properties (Lesmes and Friedman, 2005). Among many studies in which Cole-Cole parameters were estimated from SIP measurements on soils and rocks, the majority employed classical deterministic inversion methods, specifically the iterative Gauss-Newton based schemes with the Levenberg-Marquardt damping for stabilization of the inverse solution (Pelton et al, 1984;Jaggar and Fell, 1988;Luo and Zhang, 1998;Kemna, 2000;Boadu and Seabrook, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The Cole-Cole model (Cole and Cole, 1941) has been found to be very useful for interpreting spectral IP (SIP) data in terms of parameters, such as chargeability and time constant, which in turn have been used to estimate various subsurface properties (Lesmes and Friedman, 2005). Among many studies in which Cole-Cole parameters were estimated from SIP measurements on soils and rocks, the majority employed classical deterministic inversion methods, specifically the iterative Gauss-Newton based schemes with the Levenberg-Marquardt damping for stabilization of the inverse solution (Pelton et al, 1984;Jaggar and Fell, 1988;Luo and Zhang, 1998;Kemna, 2000;Boadu and Seabrook, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The IP method was initially applied to the characterization of metallic mineral ore bodies (Pelton et al ). The technique has also been used to characterize sedimentary rocks in terms of their surface area and other hydrogeological properties (Vanhala and Soininen ; Borner et al ; Boadu and Seabrook ). Other uses have included the detection of buried metallic objects such as waste drums (Weller et al ; Chambers et al ), UXO (Daily et al ) and pipelines (Parra ).…”
Section: Electrical Impedance Tomographymentioning
confidence: 99%
“…Boadu and Seabrook (2000) [21] used a double Cole-Cole model to explain a laboratory measurement on the soil samples which showed a frequency dependent electrical response (FDER). They have demonstrated that the FDER resistivity and phase spectra of the soil contain valuable information about its porosity, hydraulic conductivity, texture, and fluid properties.…”
Section: Introductionmentioning
confidence: 99%